Their Eyes Were Watching God: reflexos de raça e gênero na (re) definição do Buildungsroman - Nigro, Cláudia Maria Ceneviva [UNESP]; Chatagnier, Juliane Camila [UNESP] (My University, 2012)
The aim of this work is to present a reading about Their Eyes Were Watching God - an African-American novel written by Zora Neale Hurston in 1937, in which is narrated the trajectory of Janie, a black girl in search of her self-discovery. Convergences and divergences between the female Bildungsroman and the tradicional coming of tradicional coming of age novels which belong to the canon will be contrasted.

Propõe-se, neste trabalho, apresentar uma leitura de Their Eyes Were Watching God - romance afro-americano escrito por Zora Neale Hurston em 1937, no qual é narrada a trajetória de Janie, uma menina negra, em busca do autodescobrimento -, de modo a contrastar as possíveis convergências e divergências entre este Bildungsroman, visto aqui como feminino, e os romances de formação tradicionais pertencentes ao cânone.
Keywords: Literatura norte-americana; Raça; Buildungsroman feminino; Gênero; Zora Neale Hurston; Their Eyes Were Watching God; Race; Gender; Female Bildungsroman